Pharmacists roles and responsibilities during epidemics and pandemics in Saudi Arabia: An opinion paper from the Saudi Society of clinical pharmacy - Hisham A. Badreldin; Shahad Raslan; Hajar Almudaiheem; Bedor Alomari; Sahar Almowaina; Hala Joharji; Mohammad Alawagi; Ahmed Al-jedai (Elsevier, 2020)
On the 2nd of March 2020, Kingdom of Saudi Arabia confirmed its first case of the coronavirus's newly emerging strain, causing coronavirus disease 2019 (COVID-19). Soon after, the number of confirmed cases started to increase nationally. In light of the emerging outbreak, all healthcare professionals, including pharmacists, began to function with maximum capacity and efforts. The Saudi Society of Clinical Pharmacy (SSCP) acknowledges the substantial impact pharmacists can play during outbreaks. Based on the existing scientific knowledge during this outbreak, the SSCP established an expert writing task force to conceptualize and draft the proposed recommendations that highlights the roles and responsibilities of pharmacists during epidemics and pandemics. The SSCP writing task force issued 28 recommendations. In addition to the national and institutional guidelines, these recommendations could serve as guidance for the impacted entities.